2020
DOI: 10.1016/j.jep.2019.112409
|View full text |Cite
|
Sign up to set email alerts
|

In vitro protective effects of plants frequently used traditionally in cancer prevention in Thai traditional medicine: An ethnopharmacological study

Abstract: Ethnopharmacological relevance: Thai traditional medicine (TTM) has been used widely in cancer management in Thailand. Although several Thai medicinal plants were screened for pharmacological activities related to cancer treatment, such evidence still suffers from the lack of linking with TTM knowledge. Aim of the study: To document knowledge and species used in cancer prevention in TTM and to preliminary investigate pharmacological activities related to the documented knowledge of twenty-six herbal drugs used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…The author found that the most frequent health issues reported by the informants were indigestion, constipation, itching, eczema, ringworm, fever, weakness, malaria, jaundice, arthritis, and bone fractures. Our study findings are well supported by previous studies done by different research groups [31][32][33].…”
Section: Use Categoriessupporting
confidence: 93%
“…The author found that the most frequent health issues reported by the informants were indigestion, constipation, itching, eczema, ringworm, fever, weakness, malaria, jaundice, arthritis, and bone fractures. Our study findings are well supported by previous studies done by different research groups [31][32][33].…”
Section: Use Categoriessupporting
confidence: 93%
“…Thailand, situated in the Indo-Burma region, is one of the world’s leading biodiversity hotspots. It harbors over 15,000 plant species, many of which are integral to traditional folk medicine practices [ 7 , 8 ]. Among these, Maclura cochinchinensis (Lour.…”
Section: Introductionmentioning
confidence: 99%
“…Plantas medicinais são utilizadas em todo o mundo para o tratamento de diversas enfermidades por diferentes populações, caracterizando-se como recursos terapêuticos que se perpetuam na sociedade por meio do conhecimento popular (LUMLERDKIJ et al, 2020;ROOS et al, 2019;YOUNESSI-HAMZEKHANLU et al, 2020). Em 2006, foi aprovada no Brasil a Política Nacional de Plantas Medicinais e Fitoterápico com o intuito de que oconhecimento tradicional acerca do uso de plantas medicinais e a diversidade biológica, cultural e étnica do país pudessem ser aproveitados no desenvolvimento de pesquisas com plantas medicinais (BRASIL, 2006).…”
Section: Introductionunclassified